Stable human cartilage progenitor cell line stimulates healing of meniscal tears and attenuates post-traumatic osteoarthritis - Desai, Salomi; Dooner, Mark; Newberry, Jake; Twomey-Kozak, John; Molino, Janine; Trivedi, Jay; Patel, Jay M.; Owens, Brett D.; Jayasuriya, Chathuraka T. (Frontiers in Bioengineering and Biotechnology, 2022)
Meniscal tearing in the knee increases the risk of post-traumatic osteoarthritis (OA) in patients. The therapeutic application of tissue-specific mesenchymal progenitor cells is currently being investigated as an emerging biologic strategy to help improve healing of musculoskeletal tissues like meniscal fibrocartilage and articular hyaline cartilage. However, many of these approaches involve isolating cells from healthy tissues, and the low yield of rare progenitor populations (<1% of total cells residing in tissues) can make finding a readily available cell source for therapeutic use a significant logistical challenge. In the present study, we investigated the therapeutic efficacy of using expanded cartilage-derived and bone marrow-derived progenitor cell lines, which were stabilized using retroviral SV40, for repair of meniscus injury in a rodent model. Our findings indicate that these cell lines express the same cell surface marker phenotype of primary cells (CD54+, CD90+, CD105+, CD166+), and that they exhibit improved proliferative capacity that is suitable for extensive expansion. Skeletally mature male athymic rats treated with 3.2 million cartilage-derived progenitor cell line exhibited approximately 79% greater meniscal tear reintegration/healing, compared to injured animals that left untreated, and 76% greater compared to animals treated with the same number of marrow-derived stromal cells. Histological analysis of articular surfaces also showed that cartilage-derived progenitor cell line treated animals exhibited reduced post-traumatic OA associated articular cartilage degeneration. Stable cell line treatment did not cause tumor formation or off-target engraftment in animals. Taken together, we present a proof-of-concept study demonstrating, for the first time, that intra-articular injection of a stable human cartilage-derived progenitor cell line stimulates meniscus tear healing and provide chondroprotection in an animal model. These outcomes suggest that the use of stable cell lines may help overcome cell source limitations for cell-based medicine.